The Print and Digital Editions of Lyn Hejinian’s My Life - Chloé Thomas (Transatlantica)
My Life by Lyn Hejinian is now regarded as an exemplary work of the Language movement. It exists in several editions: first published in 1980, it was amended in 1987. A sequel, My Life in the Nineties, was then published in 2003, and, in 2013, Wesleyan University Press released My Life and My Life in the Nineties, collecting the 1987 and 2003 books, but leaving aside an addendum, “What’s Missing from My Life,” and not allowing to visualize the variants between the 1980 and 1987 versions. In 2015, a digital edition was programmed and made available online by Daniel Carter. This paper considers the various versions of My Life and describes their effects on scholarly and pedagogical work on the text, as well as on its position in the American poetic canon. It eventually suggests further ways of editing My Life digitally, focusing on the openness and paratactic construction of the text.